2009
DOI: 10.1007/s00198-009-0988-9
|View full text |Cite
|
Sign up to set email alerts
|

Femoral bone mineral density reflects histologically determined cortical bone volume in hemodialysis patients

Abstract: Summary We evaluated the associations between dual energy X-ray absorptiometry (DXA) and histologically determined cancellous and cortical bone volume by controlling for vascular calcifications and demographic variables in hemodialysis (HD) patients. Femoral bone mineral density (f-BMD) was associated with cortical porosity. Introduction Assessment of bone mass in chronic kidney disease patients is of clinical importance because of the association between low bone volume, fractures, and vascular calcificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
4
14
0
2
Order By: Relevance
“…This study supports recent histomorphometric [25, 26, 37, 38] and imaging studies [16, 17, 27, 39, 40] that have reported changes in cortical bone microarchitecture in individuals with CKD. In a cross-sectional study involving 38 dialysis patients, Adragao et al [25] reported high cortical porosity in 57% and reported a significant inverse relationship between femoral bone mineral density and cortical porosity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study supports recent histomorphometric [25, 26, 37, 38] and imaging studies [16, 17, 27, 39, 40] that have reported changes in cortical bone microarchitecture in individuals with CKD. In a cross-sectional study involving 38 dialysis patients, Adragao et al [25] reported high cortical porosity in 57% and reported a significant inverse relationship between femoral bone mineral density and cortical porosity.…”
Section: Discussionsupporting
confidence: 90%
“…However, relatively few studies have endeavoured to use histomorphometry [25, 26] or micro-CT of bone trephine samples, or utilised non-invasive techniques [16, 17, 27] to assess cortical microarchitecture and porosity in patients with CKD G5, 5D or after kidney transplantation. In the current study, 50% of patients had changes consistent with high bone turnover on histomorphometry, accompanied by elevated PTH values, but all participants had markedly abnormal cortical microarchitecture assessed by micro-CT with relatively preserved trabecular structural parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported decreased BMD in patients on dialysis (1113), but although BMD measurements have been found useful for screening or assessing fractures (6) only few larger longitudinal studies are available on dialysis patients (14,15). The pattern of bone loss may be changing with the quality and duration of dialysis treatment and the age of the dialysis population.…”
Section: Introductionmentioning
confidence: 99%
“…La DMO ne peut donc pas apporter d'élément d'orientation diagnostique en faveur d'une HPT, d'une OA ou d'une OM dont les traitements restent très différents [37]. Enfin, la DMO vertébrale est souvent faussée par les calcifications aortiques ou intervertébrales et il faut certainement privilégier le site du col du fémur et du poignet [38]. Pour toutes ces raisons, la DMO n'est pas prescrite systématiquement, mais uniquement en cas de pathologie fracturaire.…”
Section: Densitométrie Osseuseunclassified